Da invisibilidade à tragicidade: percepções sobre a representatividade de mulheres lésbicas e bissexuais nas séries - Santos, Millena Siqueira dos (2022)
Considering the exponential increase of discussions about audiovisual representativeness - especially after the massive growth of streaming services - it is pertinent to think about the impacts that these representations - or the absence of them - can cause on viewers. Thus, the present work has as its main objective to unveil the meanings behind the perceptions of lesbian and bisexual women about the representativeness of this group in the universe of TV shows. To this end, the methodology used relies on the realization of reflective interviews with a lesbian woman and a bisexual woman and, later, on the organization of the contents of these interviews in units of meaning and constellations. As a result, four constellations were elaborated, based on the speeches of the participants: “Nonrepresentation of lesbian and bisexual women”; “Production and reproduction of stereotypes”; “Impacts of representation” and “Possible strategies”, each one covering its respective units of meaning. It can be inferred, therefore, that the representation of lesbian and bisexual women, in its scarcity and materialization, directly impacts the viewers, expanding or restricting the range of possibilities they project for the future